Peran Layanan Home Visit pada Pelaksanaan Pembelajaran Tatap Muka Pasca Masa Pandemi Covid-19 - Denikit Nurin Aulia; Muhammad Arif Maulana; Mahmuddah Dewi Edmawati (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
The Covid-19 pandemic has had a considerable effect on the development of student learning. Where guidance and counseling teachers in the implementation of face-to-face learning after the Covid-19 pandemic still find many problems that occur in students. Such as a decrease in learning achievement, a decrease in student learning motivation, addiction to online games, the influence of associations, and students who are still carried away with habits during online learning so that in face-to-face learning students still feel lazy to come to school. These factors trigger the number of students who skip class. So that guidance and counseling teachers choose home visit services as a support service used to help students in finding solutions and overcoming the problems they experience. The purpose of this study is to determine the role of home visit services in the implementation of face-to-face learning after the Covid-19 pandemic. This research uses a descriptive qualitative method with case study techniques. This research took place at SMK Muhammadiyah 1 Sukoharjo. The results of this study show that home visit services have a fairly large role in alleviating problems that occur in students. With the home visit service, student problems can be immediately handled and alleviated. So that it can help the smooth and successful learning process in schools.